2012 Update on global prevention of folic acid–preventable spina bifida and anencephaly. Issue 10 (2nd September 2013) - Youngblood, Monica E.; Williamson, Rebecca; Bell, Karen N.; Johnson, Quentin; Kancherla, Vijaya; Oakley, Godfrey P.
<x xml:space="preserve">Abstract</x> BACKGROUND Folic acid was proven in 1991 to prevent most cases of spina bifida and anencephaly. In 2008, less than 10% of folic acid–preventable spina bifida and anencephaly (FAPSBA) was prevented through folic acid fortification programs. This study updates the global estimates of the proportion of FAPSBA prevented with various types of folic acid fortification as of 2012. METHODS For each country, we estimated the annual birth prevalence of FAPSBA and the daily amount of folic acid consumed from mandatory folic acid fortification programs. Assuming in Model I (our original Bell and Oakley model) that it required 400 μg, and in Model II (a new model), 200 μg of folic acid daily for total prevention of FAPSBA, we estimated the percentage of FAPSBA being prevented in each country by fortification. RESULTS Using the original model, we estimate that 15% of FAPSBA is being prevented in 2012, compared with 2006 (6.8%) and 2008 (9.1%). We estimate in our new model that 25% of FAPSBA is being prevented. CONCLUSION We estimate an increasing prevention of FAPSBA in the world through folic acid fortification, yet the pace is slow. Our new model estimates that only 25% prevention and reminds us that there remains a lot of work to do in countries that do not implement mandatory fortification, which is key to achieving global and total prevention. If we are to prevent all FAPSBA, there is an urgent need to build the global political will to find sufficient resources to aid in this effort. Birth Defects Research (Part A) 97:658–663, 2013. © 2013 Wiley Periodicals, Inc.